2021
DOI: 10.3389/fmed.2021.663494
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-Up of Corneal Biomechanical Changes After Accelerated Transepithelial Corneal Cross-Linking in Pediatric Patients With Progressive Keratoconus

Abstract: Aims: This study aimed to investigate the corneal biomechanical changes and topographic outcomes of accelerated transepithelial corneal cross-linking (ATE-CXL) in pediatric progressive keratoconus.Methods: In this prospective longitudinal study, 31 eyes of 28 pediatric patients with keratoconus (21 boys and 7 girls; mean age, 14.35 ± 2.68 years) undergoing ATE-CXL (epithelium-on procedure with 45 mW/cm2 for 320 s) were included. Corvis ST was used to measure dynamic corneal response parameters at baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A third study, however, did not find a change of SP-A1 in 18 patients that were followed-up for up to 4 years after CXL according to the Dresden protocol 13. An increase in SP-A1 was also observed postoperatively in transepithelial accelerated CXL 17. An increasing corneal stiffness after CXL seems plausible, as CXL has been reported to result in an increase in collagen fiber diameter of about 12% in the anterior corneal stroma 18.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A third study, however, did not find a change of SP-A1 in 18 patients that were followed-up for up to 4 years after CXL according to the Dresden protocol 13. An increase in SP-A1 was also observed postoperatively in transepithelial accelerated CXL 17. An increasing corneal stiffness after CXL seems plausible, as CXL has been reported to result in an increase in collagen fiber diameter of about 12% in the anterior corneal stroma 18.…”
Section: Discussionmentioning
confidence: 96%
“…13 An increase in SP-A1 was also observed postoperatively in transepithelial accelerated CXL. 17 An increasing corneal stiffness after CXL seems plausible, as CXL has been reported to result in an increase in collagen fiber diameter of about 12% in the anterior corneal stroma. 18 The current study found comparable values preoperatively and postoperatively for SP-A1 within the first months after CXL, a slightly higher SP-A1 value after 11 months and a significantly higher SP-A1 value 23 months after CXL.…”
Section: Discussionmentioning
confidence: 99%
“…Kmax increased at 1 month after epi-on and epi-off CXL, but BCVA also increased. In Weijun Jian's study, the Kmax values were 60.10 ± 7.51 D preoperatively and 61.42 ± 8.92, 61.17 ± 7.96, and 60.02 ± 7.58 D at 1, 6, and 12 months after accelerated transepithelial CXL ( P =0.05), respectively [ 22 ]. Kmax in the early postoperative period was also higher than that before surgery.…”
Section: Discussionmentioning
confidence: 99%